Diameter Increment of Remnant Stands in Logged-Over Forest in Papua - relawan kuswandi; Julius Dwi Nugroho (Jurnal Wasian, 2019)
Diameter increment is an important information used to set silvicultural prescription that plays a crucial role in sustainable forest management. Therefore, this research was aimed to analyze diameter increment of remnant stands in selectively logged forest in Papua.  The dataset was acquired from permanent sample plots in logging concessions of PT  Tunas Timber Lestari (TTL), PT  Wapoga Mutiara Timber (WMT) dan PT Manokwari Mandiri Lestari (MML). The diameter measurements were conducted annually for 6 – 9  years on three 1 ha permanent plots. Diameter increment was calculated by measuring a gap between trees diameter in year t+1 and year t. The results showed that the average diameter increment of commercial species groups in those areas were 0.56 cm/yr, 0.59 cm/yrand 0.65 cm/yr, respectively. These increments were smaller than the increment assumption of Indonesian Selective Logging (TPTI) i.e. 1.00 cm/yr. The diameter increment distribution based on diameter classes showed different patterns among sites. The diameter increment distribution in PT MML and WMT increased with the increasing diameter, otherwise those in PT TTL tend to decrease with the increasing diameter class.Keywords: logged-over forest, species group, Papua, diameter increment